EFFORTS TO IMPROVE LITERACY AND NUMERACY AT THE PRIMARY EDUCATION LEVEL IN INDONESIA - Muryanti; Andriani Sariwardani; Umalihayati; Ratna Dewi; Suandi Silalahi (Cakrawala Pedagogik, 2025)
Literacy and numeracy skills are important foundations in the learning process at the primary education level. Literacy includes not only the ability to read and write, but also the understanding and effective use of written information. Meanwhile, numeracy involves the ability to use basic math concepts in everyday life. Although crucial, the results of international assessments such as PISA show that Indonesian students' literacy and numeracy skills are still low. To address this, various policies have been implemented, including the implementation of the National Assessment and the implementation of the Merdeka Curriculum. This paper presents a narrative literature study with a descriptive-qualitative approach of 35 SINTA and international indexed journal articles from 2020-2025. The results of the study show that effective strategies in improving literacy include the use of picture storybooks, contextual learning, digital technology, and cross-subject literacy. Numeracy improvement is helped by manipulative media, contextual approaches such as PMRI and digital-based educational games. Supporting factors such as teacher training and parental involvement play an important role, while key challenges include limited resources and teacher competencies. This study suggests the integration of innovative and collaborative approaches in learning design.